AB0276 Characteristics of Patients with Early Rheumatoid Arthritis (ERA) Over Time: Data from the Catch Cohort Demonstrate that More Patients Achieve Remission in Recent Years. (9th June 2015) - Pope, J.E.; Haraoui, B.P.; Boire, G.; Hitchon, C.; Thorne, C.; Tin, D.; Keystone, E.; Bykerk, V.P.
Abstract : Background: It appears that in early rheumatoid arthritis (ERA), outcomes are improving due to the changing RA phenotype, earlier identification of patients due to the ACR/EULAR 2010 RA criteria, treating to a target (T2T), and/or early introduction of DMARDs. Objectives: To determine if baseline and one year characteristics of ERA patients are changing over time in a large cohort, including remission rates. Methods: The Canadian Early Arthritis Cohort (CATCH) started in 2003 and expanded to 23 sites that enrol patients with suspected or proven ERA with less than one year of arthritis. The data including baseline and one year: % meeting RA criteria, DAS28, RF, anti-CCP, Xrays, DMARD and biologic treatment were analyzed comparing patients enrolled before 2010 (prior to revised RA criteria and T2T widespread adoption) compared to recent patients enrolled from 2010 to 2014 (later cohort) to determine if ERA outcomes are different. Results: 701 patients in the early and 862 in the later cohort had baseline and 12 months data. Table : Comparison of Remission at 12 months in early and later cohorts years shows outcomes. Baseline characteristics were similar (except less anti-CCP positive in later cohort) but more patients were in remission (DAS28<2.6) in the later cohort despite slightly less Mtx and biologic use by one year. Conclusions: In an ERA cohort, there were more patients in remission at one year in the later cohort. The reasons for this could be due to: slightly earlier time to first visit, less anti-CCP positive and % meeting RA criteria in the later cohort, and site differences (more sites were added over time and may vary in their initial treatment including subcutaneous optimal dose methotrexate and/or initial treatment with combination DMARDs). Others have shown that effective early DMARD treatment strategies in ERA have decreased biologics use (1). References: Kuijper et al. Better Functional Ability with Less Biologicals 2 years after Induction with Combination DMARD Therapy versus Methotrexate. Abstract #2815, ACR Boston 2014. Disclosure of Interest: J. Pope Grant/research support from: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since inception of CATCH. As of 2011, further support was provided by Hoffmann-La Roche Ltd., United Chemicals of Belgium (UCB) Canada Inc., Bristol-Myers Squibb Canada Co., Abbott Laboratories Ltd., and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.)., B. Haraoui: None declared, G. Boire: None declared, C. Hitchon: None declared, C. Thorne: None declared, D. Tin: None declared, E. Keystone: None declared, V. Bykerk: None declared